A narrativa sonora de Cadão Volpato: um diálogo entre música e literatura a partir de Walter Benjamin - Nogueira, Abraão Carvalho (2023)
The writer Cadão Volpato (1956-) produced two of his works articulating themes that transited between literature and music, and for this reason, they were chosen with the perspective of developing a study regarding the characteristics of his poetic. Volpato develops an elaboration in writing through a language based on sonorous and musical signs and transforms them into allegory in the course of his literary narrative. From this perspective, we pretend to elaborate an interpretation of sonorous narrative in the works The discs of twilight (2017), book of tales, and In the shade of viaducts in flower (2018), book of memoirs. These works have in common in their creative processes the development of a literary activity through of sonorous and musical signs as relevant characteristics in their poetic. The theoretical dialogue developed, found in the work Lessons of Poetic (2018), by Paul Valéry, significative orientations of study in relation to literary interpretation procedures. Through the considerations about the conception of poetic in Valéry, we dialogue with some aspects of Walter Benjamin’s philosophy of art, and with authors that have established dialogue with discussed questions for this author. From this theoretical perspective, we seed to subsidize the interpretative procedures of the literary works of Cadão Volpato chosen for this study.